Effects of a single‐dose methylphenidate challenge on resting‐state functional connectivity in stimulant‐treatment naive children and adults with ADHD. Issue 15 (4th July 2022) - Kaiser, Antonia; Broeder, Caroline; Cohen, Jessica R.; Douw, Linda; Reneman, Liesbeth; Schrantee, Anouk
Abstract: Prior studies suggest that methylphenidate, the primary pharmacological treatment for attention‐deficit/hyperactivity disorder (ADHD), alters functional brain connectivity. As the neurotransmitter systems targeted by methylphenidate undergo significant alterations throughout development, the effects of methylphenidate on functional connectivity may also be modulated by age. Therefore, we assessed the effects of a single methylphenidate challenge on brain network connectivity in stimulant‐treatment naïve children and adults with ADHD. We obtained resting‐state functional MRI from 50 boys (10–12 years of age) and 49 men (23–40 years of age) with ADHD (DSM IV, all subtypes), before and after an oral challenge with 0.5 mg/kg methylphenidate; and from 11 boys and 12 men as typically developing controls. Connectivity strength (CS), eigenvector centrality (EC), and betweenness centrality (BC) were calculated for the striatum, thalamus, dorsal anterior cingulate cortex (dACC), and prefrontal cortex (PFC). In line with our hypotheses, we found that methylphenidate decreased measures of connectivity and centrality in the striatum and thalamus in children with ADHD, but increased the same metrics in adults with ADHD. Surprisingly, we found no major effects of methylphenidate in the dACC and PFC in either children or adults. Interestingly, pre‐methylphenidate, participants with ADHD showed aberrant connectivity and centrality compared to controls predominantly in frontal regions. Our findings demonstrate that methylphenidate's effects on connectivity of subcortical regions are age‐dependent in stimulant‐treatment naïve participants with ADHD, likely due to ongoing maturation of dopamine and noradrenaline systems. These findings highlight the importance for future studies to take a developmental perspective when studying the effects of methylphenidate treatment. Abstract : We investigated the effects of the stimulant methylphenidate on functional connectivity in stimulant‐treatment naïve children and adults with ADHD, as well as typically developing controls. We found that methylphenidate modulated connectivity metrics primarily in the striatum and thalamus, with little effect on frontal regions. Importantly, opposing effects were found on network connectivity in children and adults in subcortical regions, possibly due to maturation of the dopamine and noradrenaline neurotransmitter systems. As such, our results increase our understanding of the effects of stimulants on brain networks in ADHD and stress the importance of taking a developmental perspective.